Clinical evaluation of Boswellia serrata (Shallaki) resin in the management of Sandhivata (osteoarthritis) - Gupta, P. K. (Medknow Publications & Media Pvt Ltd, 2011)
Sandhigata vata is described under Vatavyadhi in all Ayurvedic texts. Charaka was the first to describe separately “Sandhigata anila”, but it was not included under 80 types of nanatmaja vatavyadhi. Osteoarthritis is the most common degenerative joint disease that begins asymptomatically in middle age with progressive symptoms in advancing age. Majority of people by the age 40 years may develop osteoarthritis, especially in weight bearing joints. Females are prone with 25% prevalence, whereas males have a prevalence of 16%. In the present study, 56 patients fulfilling the diagnostic criteria of Sandhigata vata, divided into two groups. Patients of first group were administered with 500 mg capsule of Shallaki, 6 g per day (in three divided doses) with lukewarm water (n=29) and the second group) capsule Shallaki as above along with local application of Shallaki ointment on the affected joints (n=23). After a course of therapy for 2 months, symptomatic improvement was observed in both the groups at various levels with promising results in the patients of first group.